ON THE DIVISOR FUNCTION OVER NONHOMOGENEOUS BEATTY SEQUENCES - ZHANG, WEI (Bulletin of the Australian Mathematical Society, 2022)
We consider sums involving the divisor function over nonhomogeneous ( $\beta \neq 0$ ) Beatty sequences $ \mathcal {B}_{\alpha ,\beta }:=\{[\alpha n+\beta ]\}_{n=1}^{\infty } $ and show that $$ \begin{align*} \sum_{n\leq N,\ n\in\mathcal{B}_{\alpha,\beta}}d(n) =\alpha^{-1}\sum_{m\leq N}d(m) +O(N^{1-1/(\tau+1)+\varepsilon}), \end{align*} $$ where N is a sufficiently large integer, $\alpha $ is of finite type $\tau $ and $\beta \neq 0$ . Previously, such estimates were only obtained for homogeneous Beatty sequences or for almost all $\alpha $ .